2020
DOI: 10.1103/physrevb.102.205408
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oxygen defects in an in-plane anisotropic transition metal dichalcogenide

Abstract: Atomic scale defects in semiconductors enable their technological applications and realization of novel quantum states. Using scanning tunneling microscopy and spectroscopy complemented by ab-initio calculations we determine the nature of defects in the anisotropic van der Waals layered semiconductor ReS2.We demonstrate the in-plane anisotropy of the lattice by directly visualizing chains of rhenium atoms forming diamond-shaped clusters. Using scanning tunneling spectroscopy we measure the semiconducting gap i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
(55 reference statements)
0
12
1
Order By: Relevance
“…For WSe 2 and ReS 2 surfaces, recent research also suggested that O interstitials are expected to be energetically favorable and can survive after annealing, though no excess charges were observed on these atomic interstitials. 39,40 Therefore, it would be reasonable to speculate that the negatively charged defect D-1 could be an acceptor-like interstitial (e.g., a C-or N- related impurity) buried in the middle (tungsten) slab of the sandwiched WSe 2 atomic layer, which cannot be directly resolved by a scanning tunneling microscope but could be knocked out by a voltage pulse applied to the microscope tip, manifesting itself as an "erasable" defect. Figure 2a shows the I−V (red filled circles) and simultaneous dI/dV (red open circles) spectra measured on top of defect D-1, revealing its electron transport characteristics.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For WSe 2 and ReS 2 surfaces, recent research also suggested that O interstitials are expected to be energetically favorable and can survive after annealing, though no excess charges were observed on these atomic interstitials. 39,40 Therefore, it would be reasonable to speculate that the negatively charged defect D-1 could be an acceptor-like interstitial (e.g., a C-or N- related impurity) buried in the middle (tungsten) slab of the sandwiched WSe 2 atomic layer, which cannot be directly resolved by a scanning tunneling microscope but could be knocked out by a voltage pulse applied to the microscope tip, manifesting itself as an "erasable" defect. Figure 2a shows the I−V (red filled circles) and simultaneous dI/dV (red open circles) spectra measured on top of defect D-1, revealing its electron transport characteristics.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…35 These sources are distinct from those examined in BP and other 2D semiconductors in the literature: for example, substitutional lattice oxygen in BP (which we do not observe) does induce in-gap states, 26 but substitutional oxygen in transition-metal dichalcogenides does not. 36,37 The metallic LDOS we observe due to oxygen dosing is consistent with the conductivity increase in the BP with physisorbed O 2 over short time scales (minutes to hours). 7 However, it is worth noting that a decrease in conductivity was also reported due to oxidation and degradation.…”
Section: ■ Defect Identification and Discussionmentioning
confidence: 99%
“…Understanding these systems is critical for the study of single-electron physics, and two-state systems are of particular relevance for emerging quantum information technology. In semiconducting devices such as photovoltaics, transistors, and diodes, individual charge states such as dangling bonds [5], individual dopants [6], and defects [7] are not electrically isolated from their environment, and it is critical to understand their effects on the global electronic structure, in particular device efficiency and noise. In this work, we measure single dopant fluctuations which give rise to variations in the surface potential of a mesoscopic metal-insulator-semiconductor (MIS) capacitor device.…”
mentioning
confidence: 99%
“…Note that band bending in thin samples is spatially limited in the z (perpendicular) direction, but if there is a localized gate (as is the case for fm-AFM), band bending also occurs in the x and y directions, meaning that there can still be an appreciable surface potential [6,18]. This is why previously-reported defects measured with fm-AFM on thin TMDC samples [7] are much larger than a single lattice site.…”
mentioning
confidence: 99%